Tri Hita Karana in Balinese Customary Law as a Basis for The Settlement of the Village Boundary Conflict in Bali - Made Hendra Wijaya; I Wayan Eka Artajaya (Fakultas Hukum, Universitas Warmadewa, 2020)
Tri Hita Karana in balinese customary law as a basis for the settlement of the village boundary conflict in bali is the title used in this reseacrh, to demonstrate that the philosophical Tri Hita Karana is an extraordinary thought to solve the problems of the Balinese people, especially to solve the problem of village boundaries in Bali. The technicalities of the philosophical Tri Hita Karana are Parhyangan, Pawongan, Palemahan, so that the Balinese only see three technicalities of Tri Hita Karana. The objectives of this study is to examine the real form of the concept of Tri Hita Karana in resolving village boundary conflicts, and to examine the role of Pekraman Village in implementing the Tri Hita Karana concept as the guardian of the life balance of the Krama/Villager of his village community. This research method uses normative methods, namely legal research that examines written law from various aspects. This research analysis used is the analytical approach to History (approach of Historical analysis). The results revealed that Balinese people in resolving their problems, especially related to village boundaries, must always hold on to the concrete steps of Tri Hita Karana, namely Parhyangan, Pawongan, and Palemahan to shape the behavior of Balinese people to bring about conflict resolution by means of family negotiations, and mutual respect and try to understand the problem by way of consensus agreement to achieve good together and create harmony.